Fiscal policy after the crisis: What role for fiscal policy in times of crisis, low interest rates and high public debts? - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2022)
In 2009, just before the full outbreak of the global financial crisis, Olivier Blanchard (2009) published an article giving a favourable appraisal of the state of macroeconomics. He came to this verdict on the basis that, after a long period of fierce theoretical debate, the discipline had converged on a model known as new consensus macroeconomics (NCM). In the models that made up NCM, fiscal policy played no role - or, to be more precise, fiscal policy had to follow a balanced-budget rule, with the task of stabilising an economy over the business cycle entrusted entirely to monetary policy (following a Taylor rule). And in the midst of the global financial crisis, Carmen Reinhart and Kenneth Rogoff (2010) proposed the figure of 90% of GDP as a threshold level for public debt which, if exceeded, would harm economic growth, leaving fiscal austerity as the best way to trigger economic recovery. Only a decade later, the economics profession now appears to have taken a very different view on fiscal policy: in order to cope with the next economic crisis, resulting from the coronavirus pandemic, most economists recommend an active fiscal policy stance and even a huge increase in debt-to-GDP levels. This paper will shed some light on these developments in economic policymaking and explore the future of fiscal policy.
Keywords: E62; H30; H62; 330; Fiscal policy; public debt; stabilisation policy